Characterising the Strain and Temperature Fields in a Surrogate Bone Material Subject to Power Ultrasonic Excitation. (16th August 2013) - Wang, D.; Lucas, M.; Tanner, K. E.
ABSTRACT The behaviour of the cancellous bone surrogate material, rigid polyurethane foam (PUF), subject to power ultrasonic vibration excitation has been studied, with the purpose of identifying a methodology to investigate the effects that ultrasonic surgical devices have on biological tissue materials. To characterise the vibrational response to ultrasonic excitation, non‐contact measurement of the full in‐plane displacement field of PUF plate specimens was performed by combining the use of an ultra‐high speed camera and 2D digital image correlation. To investigate the thermal response, an infrared camera was used in real time to detect the temperature field. The measured surface displacement and strain fields of the PUF specimens and the thermal response are compared with data from an analytical model, and two different finite element models using Abaqus and PZFlex. The close agreement between calculated and measured data provides initial confidence in the use of the models for predicting the effects of ultrasonic excitation on tissue materials. The measurement data demonstrate the success of the experimental method for measuring vibrational responses in a hard tissue surrogate material at the ultrasonic frequencies associated with power ultrasonic surgical devices.